(untitled) (Czech Journal of International Relations, 2015)
G. John Ikenberry: Liberal Leviathan. The Origins, Crisis, and Transformation of the American World Order. 1st ed. Princeton and Oxford: Princeton University Press, 2011, 392 stran, ISBN 978-0-691-12558-9. Robert Kagan: The World America Made. New York: Alfred A. Knopf, 2012, 149 stran, ISBN 978-0-307-96131-0. Henry A. Kissinger: The World Order. Reflections on the Character of Nations and the Course of History. 1st ed. New York: Penguin Press, 2014, 432 stran, ISBN 978-1-594-20614-6. Charles A. Kupchan: No One’s World. The West, the Rising Rest, and the Coming Global Turn. 1st ed. Oxford and New York: Oxford University Press, 2012, 272 stran, ISBN 978-0-199-73939-4.